Implementasi Internet Protocol Versi 6 Pada Jaringan VoIP Berbasis Session Initiation Protocol - Mhd. Tri Arief; Ilham Faisal; Divi Handoko (Universitas Harapan Medan, 2023)
Analyzing the difference in performance values generated by the IPv4 protocol and the IPv6 protocol VoIP services on a WAN network using a bandwidth of 128 Kbps. Session Initiation Protocol (SIP) is one of the protocols commonly used in Voice Over Internet Protocol (VoIP) telecommunications. SIP is a signaling protocol developed by the Internet Engineering Task Force (IETF) under the label RFC3261. In a telephone call using IPv4 and IPv6 with a distance of 3 meters concluded that IPv6 is better with a bandwidth of 55.1 Kb and Packet Traffic of 140 compared to IPv4 with a result of 35.1 Kbps and Packet Traffic of 150. Computer network topology is a network arrangement in which each part is interconnected with each other through physical media such as cables and optical fiber.